Language Learners’ Attitudes Toward Online and Face-To-Face Language Environments - Alhamami, Munassir (Frontiers in Psychology, 2022)
Finding a valid and reliable theoretical construct to elicit and analyze attitude is crucial to understand learners’ attitudes. Searching attitude is a major research area in social psychology. This researcher uses the Attitude toward Behavior (AB) construct proposed by Ajzen, a social psychologist, to elicit, examine and predict language learners’ attitudes toward face-to-face language learning (FLL) and online language learning (OLL). Data were collected using two instruments: two types of questionnaires, and interviews of two groups: FLL (n = 681) and OLL (n = 287). The results of the questionnaires and interviews data show that the use of the AB social psychology concept as a theoretical framework to design the questionnaires is significant in understanding the factors that influence the participants’ attitudes and in predicting their attitudes in the different learning environments. A comparison of the results of FLL group and OLL group demonstrates that the participants have more positive attitude toward learning the language in a face-to-face setting than in an online setting. The results of the study suggest the use of a mixed-method design and borrowing a valid and reliable construct to support the assessment of learners’ attitudinal beliefs about language learning. Also, policymakers should consider students’ attitude toward the learning environment while designing program curriculum.